Rising nitrogen deposition leads to only a minor increase in CO2 uptake in Earth system models - Sian Kou-Giesbrecht; Vivek K. Arora; Chris D. Jones; Victor Brovkin; Tomohiro Hajima; Michio Kawamiya; Spencer K. Liddicoat; Alexander J. Winkler; Sönke Zaehle (Communications Earth & Environment)
Abstract Current frameworks for evaluating biogeochemical climate change feedbacks in Earth System Models lack an explicit consideration of nitrogen cycling in the land and ocean spheres despite its vital role in limiting primary productivity. As coupled carbon-nitrogen cycling becomes the norm, a better understanding of the role of nitrogen cycling is needed. Here we develop a new framework for quantifying carbon-nitrogen feedbacks in Earth System Models and show that rising nitrogen deposition acts as a negative feedback over both land and ocean, enhancing carbon dioxide (CO2) fertilisation in a model ensemble. However, increased CO2 uptake due to rising nitrogen deposition is small relative to the large reduction in CO2 uptake when coupled carbon-nitrogen cycling is implemented in Earth System Models. Altogether, rising nitrogen deposition leads to only a minor increase in CO2 uptake but also enhances nitrous oxide (N2O) emissions over land and ocean, contributing only marginally to mitigating climate change.